Cinema Today : A Conversation with Thirty-nine Filmmakers from around the World - Oumano, Elena (Book collections on Project MUSE., 2010)
In Cinema Today, Elena Oumano has ingeniously crafted a conversation from her personal and individual interviews with a distinguished group of international cinema legends. She follows a lively symposium-in-print format, with the filmmakers' words and thoughts grouped together under various key cinema topics. Collectively these artists reflect on and explore issues and concerns of modern filmmaking, from the practical to the aesthetic, including the process, cinematic rhythm and structure, and the many aspects of the media: business, the viewer, and cinema's place in society.